Revealing the pharmacological effect and mechanism of darutoside on gouty arthritis by liquid chromatography/mass spectrometry and metabolomics - Wang, Jing; Sun, Yan-Chun (Frontiers in Molecular Biosciences, 2022)
Darutoside is a diterpenoids compound with significant anti-inflammatory activity, however the pharmacological action and mechanism are still unclear. Metabolomics strategy was used to uncovering the pharmacological action and effective mechanism of darutoside against acute gouty arthritis rats. Liquid chromatography coupled with mass spectrometry technique was performed to explore the serum metabolites and potential pathways. We found that darutoside can up-regulate the level of glutamate, alanine, chenodeoxycholic acid, 1-methyladenosine, aspartic acid, citric acid, and down-regulate the level of valine, isoleucine, glutamine, alanyl-threonine, pyruvic acid, gamma-aminobutyric acid, uric acid. Metabolic pathway analysis showed that the therapeutic effect of darutoside was involved in amino acid metabolism, sugar metabolism, fatty acid metabolism, energy metabolism, purine metabolism and butanoate metabolism. It indicated that darutoside protect against acute gouty arthritis by regulating the expression of the key protein targets. It revealed that the mechanism of darutoside on acute gouty arthritis, which may be leading to the changes of serum metabolites, metabolic pathways and key protein targets to improve immune system response, inhibit oxidative stress and inflammatory response. It provides a novel method for molecular mechanisms of natural product in the disease treatment.